2017
DOI: 10.14744/nci.2017.14227
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Evaluation of Living Donor Liver Volume in Living Donor Liver Transplantation

Abstract: OBJECTIVE:The aim of the present study was to retrospectively evaluate the difference between the preoperative estimated volume and the actual intraoperative graft volume determined in donor right hepatectomies and to evaluate the possible effect of age, gender, and body mass index on the difference.METHODS:A total of 225 donor hepatectomies performed at the center between 2016 and 2017 were evaluated for the study. Left hepatectomies and left lateral segmentectomies were excluded from the analysis. As a resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Nevertheless, the study showed a statistically significant change between all three measurements, as well as a statistically significant difference in liver volume between inspiratory and expiratory states. These results form the basis of the arguments put forth in this discussion, and other studies assessing preoperative planning and intraoperative volume show corroborating evidence [ 25 , 51 , 52 , 58 , 60 62 ]. Consistent with the recommendations to keep the number of animal experiments as low as possible, e.g., 3Rs (reduction, replacement, refinement) and PREPARE guidelines we chose to not perform additional experiments since the current number of animals was sufficient for statistical evaluation with the current focus of the study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Nevertheless, the study showed a statistically significant change between all three measurements, as well as a statistically significant difference in liver volume between inspiratory and expiratory states. These results form the basis of the arguments put forth in this discussion, and other studies assessing preoperative planning and intraoperative volume show corroborating evidence [ 25 , 51 , 52 , 58 , 60 62 ]. Consistent with the recommendations to keep the number of animal experiments as low as possible, e.g., 3Rs (reduction, replacement, refinement) and PREPARE guidelines we chose to not perform additional experiments since the current number of animals was sufficient for statistical evaluation with the current focus of the study.…”
Section: Discussionsupporting
confidence: 83%
“…In regards to preoperative planning, differences in preoperative measured volume and in situ volume have been recorded previously. In volumetric analysis of living donor transplant livers, Baskiran et al described significant reductions between estimated and intraoperative volumes [ 52 ], and correctly stressed the need for surgical awareness to prevent small-for-size and large-for-size errors. The current study should underline this finding, and further emphasize that liver volume must be critically re-evaluated in the intraoperative setting, especially in laparoscopic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Some studies have reported an error ratio of 10% to 20%. [8][9][10] In our study, the mean error ratio was 6.59+4.623%.…”
Section: Discussionmentioning
confidence: 41%
“…Baskiran et al 10 reported that age and BMI had a significant impact on the error percentage while gender did not. In present study, donor's age and gender didn't have any significant agreement with error percentage (p=0.500, 0.523 respectively) and overestimation or underestimation (p=0.881,0.740 respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Volume estimation accuracy of a healthy organ or a pathological structure influences patient management outcome (1,2). Difficulties and inaccuracies encountered in clinical volume assessments compel clinicians to rely on image-assisted methodology (3).…”
Section: Introductionmentioning
confidence: 99%